Effectiveness Of Lemon Aromatherapy In Reducing Labor Anxiety Active Phase In Work Area Bukit Sari Public Health Center - Ebtanastuti, Trisna; Hanifa, Fatya Nurul; Ananti, Yustina (Universitas Prima Indonesia, 2025)
Abstract: Anxiety in labor is a common feeling of fear that affects many women. High levels of anxiety can cause pain and impact contractions and the birth canal's opening. To reduce this anxiety, lemon aromatherapy may help by calming muscles and nerves. The study aimed to determine if lemon aromatherapy effectively lowers anxiety in pregnant women during early labor. Study methods: study design that uses a control group and a quasi-experimental pre- and post-test design. There are 46 active phase I maternity moms in the research group. Total sampling is the method of sampling. There were 23 participants in each group. Frequency distribution table for univariate data analysis, MC Nemar test and chi square test for bivariate analysis. Results: According to the study's findings, 23 individuals (100%) in the control group and the intervention group had moderate anxiety levels before to the intervention. Following the session, anxiety levels in the control group of 13 individuals (56.5%) and the intervention group of 18 individuals (78.3%) dropped to mild levels. The chi square test findings between the intervention group and the control group showed a p-value of = 0.046 (p<0.05), while the Mc Nemar test results showed a p-value of 0.000 (p<0.05). Conclusion: Lemon aromatherapy has an impact on maternity moms' anxiety levels during the initial active period.